The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.minpro.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-microencapsulation for preventing pyrite oxidation

Abstract: The oxidation of pyrite causes the formation of acid mine drainage polluted by heavy metals. This paper proposes carrier-microencapsulation (CME) for preventing pyrite oxidation. In CME, an organic agent is used as an in-situ carrier for transporting Ti from Ti minerals to the pyrite surface through an aqueous phase. Then, the organic carrier is decomposed and Ti(OH) 4 or TiO 2 film is formed on the pyrite surface as a protective coating against oxidation.To demonstrate the effect of CME on pyrite oxidation, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…Current density is the anodic current of the working electrode in the working area of 1.10 cm 2 . From these results, the anodic currents of Si-Cat treated pyrite samples (1,6, and 12 h) are lower than that of the untreated pyrite. Because the anodic current represents the oxidation rate, the lower anodic currents of Si-Cat treated pyrite samples mean that the oxidation rates of these samples are lower than that of the untreated pyrite.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Current density is the anodic current of the working electrode in the working area of 1.10 cm 2 . From these results, the anodic currents of Si-Cat treated pyrite samples (1,6, and 12 h) are lower than that of the untreated pyrite. Because the anodic current represents the oxidation rate, the lower anodic currents of Si-Cat treated pyrite samples mean that the oxidation rates of these samples are lower than that of the untreated pyrite.…”
Section: Resultsmentioning
confidence: 82%
“…), stirred with a magnetic stirrer at 100 rpm. After a predetermined stirring time (1,6, and 12 h), the working electrode was air dried for 30 min, and used for electrochemical measurements in 0.10 mol/L sulfuric acid.…”
Section: Electrochemical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The metal ion released from the complex hydrolyzes to form a thin layer of metal oxide or hydroxide on the pyrite surface [17,18]. In the previous papers, it was reported that the layer formed by CME treatment is hydrophilic and protective against oxidation;…”
Section: +mentioning
confidence: 99%